Creation of cellular models for the analysis of sodium-dependent phosphate transporter NaPi2b, a potential marker for ovarian cancer - Gryshkova, V.S.; Lituyev, D.S.; Filonenko, V.V.; Kiyamova, R.G. (Інститут молекулярної біології і генетики НАН України, 2009)
The aim of present study was to develop a model for a functional analysis of a recently identified marker of the ovarian cancer - sodium-dependent phosphate transporter NaPi2b. For this purpose, we have created HEK293 stable cell lines expressing wild type or mutant forms of NaPi2b (T330V substitution in a large extracellular loop and a 6 amino acid residues deletion in the C-terminal cytoplasmic tail), revealed in the ovarian cancer cell lines. The expression of wild type and mutant forms NaPi2b in the stable cell lines created was confirmed by Western-blot analysis with monoclonal antibodies against NaPi2b. The cellular models described here will be useful for studying the function of sodium-dependent phosphate transporter NaPi2b in health and disease.